Analisis Validitas dan Reliabilitas Hasil Belajar pada Mata Pelajaran IPA Siswa Kelas 5 SDN Kalideres 06 Pagi - Magdalena, Ina; Nabilah, Nabilah; Lestari, Linda; Afrillia, Nanda Nurul; Zhalilla, Zhilan (TSAQOFAH, 2023)
The purpose of this study was to develop a grade V science achievement test. The aim of this study was to explain the development stages of this study. Namely Validity and Reliability. This type of research uses Developmental Research (Development). And this research uses a 4D development model which consists of the defining stage, the design stage, the development stage and the deployment stage. Given the conditions in which it is not possible. The subject in this study was a science learning achievement test instrument in the form of a multiple choice test with a total of 10 items. Data collected using the test method. The data that has been obtained is then analyzed for validity and reliability. And data collection techniques in the form of observation, interviews, documentation and tests. And the type of research used is quantitative research with descriptive methods. The results obtained in this study of the 10 PG questions for 15 students only 5 items were valid, while the other 4 items were declared invalid (dropped) and 1 item could not be counted. Then look for the reliability of the questions and only valid ones are used. Based on the results of the analysis using the Kr20, Kr21, and also CA formulas, it is obtained that the r table is 0.46 so that the reliability criterion for this question is high.